The resilience of pioneer crops in the highlands of Central Asia: Archaeobotanical investigation at the Chap II site in Kyrgyzstan - Motuzaite Matuzeviciute, Giedre; van Unen, Manon; Karaliute, Ruta; Tabaldiev, Kubatbek (Frontiers in Ecology and Evolution, 2022)
This paper presents our archaeobotanical research results from an occupation horizon of the Chap II site left by the earliest known farming community in the Central Tien Shan mountains in the current territory of Kyrgyzstan. The archaeobotanical samples were recovered from well-defined contexts in domestic waste pits, house floors, fireplaces, and an oven, all of which date to a narrow period of occupation between 2474-2162 cal BCE (based on n-14 AMS dates). The archaeobotanical assemblage is dominated by the SW package crops of bread wheat and naked barley. Those are the only species to have progressed further east across the mountain ranges of Central Asia during the earliest wave of crop dispersal. However, other species in small quantities were also identified at the Chap II site, such as T. durum/turgidum, T. carthlicum, possibly glume wheats and hulled barley. Here we argue that the dominant compact morphotypes seen only in bread wheat and naked barley caryopses hint towards a selection for the specific adaptive traits of cultigens that enabled a successful agriculture in high altitude ecogeographies. Large variation in cereal caryopses size possibly indicate that crops endured stress (e.g. insufficient nutrients, water or other) during plant development. More research is needed for a better understanding of the developmental plasticity between different crop species and the formation of unique landraces in diverse environmental niches in the past.